Prediction of Carbide Precipitation Using A Combined Partial Equilibrium - Para-Equilibrium - Lever Rule Approximation in Automobile Gear Materials. (May 2019) - Zhang, Hongwei; Nakajima, Keiji; Su, Mengmeng; Gao, Shaoshao; Lei, Hong; Wang, Qiang; He, Jicheng
Abstract: The carbide precipitation nature of an automobile gear material, i.e. Fe-C-Mn-Si-Cr-Mo alloy, during carburization and element addition process are investigated through PE+PA+LR prediction. Results show that, carburization process greatly increases the amount of cementite as well as the hardness index at the surface part. Besides, the addition of Ti and V helps to formation of TiC and (V, Mo)C carbides but suppress the precipitation of cementite, which contributes equivalent hardness at surface and lighter weight to the alloy.